2008
DOI: 10.1093/scan/nsn030
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the motivational brain: effects of implicit power motivation on brain activation in response to facial expressions of emotion

Abstract: This study tested the hypothesis that implicit power motivation (nPower), in interaction with power incentives, influences activation of brain systems mediating motivation. Twelve individuals low (lowest quartile) and 12 individuals high (highest quartile) in nPower, as assessed per content coding of picture stories, were selected from a larger initial participant pool and participated in a functional magnetic resonance imaging study during which they viewed high-dominance (angry faces), low-dominance (surpris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 46 publications
3
54
0
Order By: Relevance
“…Based on these findings it is suggested that the nucleus accumbens, putamen and caudate nucleus are sensitive to processing close matchings between needs and rewards. These results are in line with findings by Schultheiss et al (2008), who reported that individuals with a high need for power show stronger activation in brain structures involved in motivation (e.g. the striatum) when watching need-congruent pictures.…”
Section: Matching Personal Needs and Rewardssupporting
confidence: 92%
“…Based on these findings it is suggested that the nucleus accumbens, putamen and caudate nucleus are sensitive to processing close matchings between needs and rewards. These results are in line with findings by Schultheiss et al (2008), who reported that individuals with a high need for power show stronger activation in brain structures involved in motivation (e.g. the striatum) when watching need-congruent pictures.…”
Section: Matching Personal Needs and Rewardssupporting
confidence: 92%
“…While potentially more relevant to the clinic, both social interaction and performance feedback were employed in this study and offer a viable platform for development of successful reward-based rehabilitation. As mentioned previously, manipulations such as perceived reward, perceived control, level of challenge, meditation, and aerobic exercise all have exhibited the capability of positively influencing learning and/or performance through modulations of the state of the learner [27][28][29][30][31][32][33][34][35][36][37][38][39][61][62]. In this regard, the current study employs monetary reward as but one of many possible motivational influences capable of enhancing the state of the learner in order to improve recovery (learning) in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…A fundamental tenet in the field of cognitive neuroscience is that reward provides motivational incentive that elicits brain states conducive to adaptive learning [27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Moreover, clinicians widely acknowledge the essential role of reward and motivation in successful rehabilitation and recovery [41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, activity in the CMS regions significantly moderates activity in other brain regions associated with moral emotion and motivation (e.g., midbrain including the ventral tegmental area, ventral striatum, insula, OFC [57][58][59][60][61]) while subjects are solving moral problems.…”
mentioning
confidence: 99%